Cloud-based Computing Adoption in Internship Management System for University Education - Thammastitkul, Akara (Naresuan University Journal: Science and Technology (NUJST), 2022)
During the COVID-19 pandemic, cloud computing became an essential tool in distance education activities. Due to pandemic restrictions, normal face-to-face internship supervision was suspended. Therefore, an online internship management system using cloud-based computing is designed and adopted. Google Suite, a public cloud computing service, was used for this development. Google Suite is a powerful platform with simple administration facilities and multi-platform compatibility and is an excellent collaboration tool widely used at universities. The proposed development approach consisted of Requirements Analysis, User Analysis, Documentation Analysis, System Function Analysis, Tool Analysis, System Implementation and Testing. Standard testing methods of heuristic evaluation and user acceptance tests were performed. The result shows that the cloud-based system for online internship management system using Google Suite has achieved excellent performance levels in terms of cost savings, user interface satisfaction, ease of use, ease of access, ease of control, ease of monitoring, ease of manageability, usefulness and usability. The proposed framework can be used as a prototype to build an educational organization cloud-based management system. Keywords: Cloud computing, Internship management system, remote education